2006
DOI: 10.1016/j.euromechflu.2006.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalent effects of added layers on steady kinematic dynamos in cylindrical geometry: application to the VKS experiment

Abstract: International audienc

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
77
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 28 publications
(77 reference statements)
9
77
3
Order By: Relevance
“…[33] allows a description of the amplitude of the magnetic vector potential by an equation similar to Eq. (10). A parametric resonance (also called swing excitation) is observed when the frequency of the perturbing velocity pattern is twice the natural frequency of the dynamo.…”
Section: -11mentioning
confidence: 99%
See 1 more Smart Citation
“…[33] allows a description of the amplitude of the magnetic vector potential by an equation similar to Eq. (10). A parametric resonance (also called swing excitation) is observed when the frequency of the perturbing velocity pattern is twice the natural frequency of the dynamo.…”
Section: -11mentioning
confidence: 99%
“…In an idealizing model the mean axisymmetric flow between counter-rotating impellers comprises two toroidal and two poloidal eddies (so-called s2t2 topology), and it is well known that this flow is able to drive a dynamo [5,6]. Various attempts in different geometries have been made (numerically as well as experimentally) in order to examine dynamo action driven by such a flow [4,[7][8][9][10][11][12][13][14][15][16][17][18][19][20]. However, so far, experimental dynamo action driven by a von Kármán-like flow is obtained only at the VKS facility and only when at least one of the flow-driving impellers is made of soft iron with a large relative permeability.…”
Section: Introductionmentioning
confidence: 99%
“…In the present experiment, fluctuations enter both multiplicatively, because of the turbulent velocity, and additively, due to the interaction of the velocity field with the ambient magnetic field. Finally, we note that both R c m and R 0 m are smaller than the thresholds computed with kinematic dynamo codes taking into account only the mean flow, that are in the range R c m = 43 to 150 depending on different boundary conditions on the disks and on configurations of the flow behind them [14,20].…”
mentioning
confidence: 99%
“…It has been also shown that in the case of a Ponomarenko or G. O. Roberts flows, the addition of an external wall of high permeability can decrease the dynamo threshold [19]. Finally, recent kinematic simulations of the VKS mean flow have shown that different ways of taking into account the sodium behind the disks lead to an increase of the dynamo threshold ranging from 12 % to 150 % [20]. We thought that using iron disks could screen magnetic effects in the bulk of the flow from the region behind the disks, although the actual behavior may be more complex.…”
mentioning
confidence: 99%
“…Previous numerical studies [13,14] compared the threshold values in configurations including and excluding the effect of fluid behind the disks. We reproduce here a similar behaviour of the threshold: using insulating boundary conditions directly on the disks yields a threshold value Rm c = 63.…”
mentioning
confidence: 99%